Negative Pressure Pulmonary Edema due to Upper Airway Obstruction in Two Dogs - Choi, D; Yang, MP; Kang, BT; Choi, M; Nam, H; Chae, Y; Koo, Y; Yun, T; Lee, D; Kim, H (Journal of the Hellenic Veterinary Medical Society, 2023)
Two dogs were referred because of chronic cough and respiratory distress. One dog (Case 1) showed severe respiratory distress and mild interstitial patterns on the thoracic radiographs after external ring prostheses were placed to support a collapsing cervical trachea. The dog had received 1 mg/kg of furosemide three times daily for 2 days to treat pulmonary edema. Although appropriate treatment was provided to resolve pulmonary edema, persistent pulmonary edema and respiratory distress had been shown. There was no evidence of cardiogenic pulmonary edema based on the physical, radiographic, and echocardiographic examinations. The other dog (Case 2) was diagnosed with tracheal collapse and bronchomalacia. In addition, mild interstitial patterns were detected on the thoracic radiographs. There was no evidence of cardiac disease based on the physical and radiographic examinations. Because these findings were suspected to indicate negative pressure pulmonary edema due to airway obstruction, Case 1 was immediately given dexamethasone for 2 days to relieve postoperative swelling. Case 2 received 0.05 mg/kg of acepromazine for sedation and endotracheal intubation with positive-pressure ventilation for 2 days. All abnormal signs, including pulmonary edema, disappeared in Case 1, but Case 2 was discharged with a mild cough. This report describes the clinical course of negative pressure pulmonary edema due to airway obstruction in two dogs. Clinicians should be aware that airway obstruction can cause fulminant non-cardiogenic pulmonary edema in dogs.